2022
DOI: 10.1093/ckj/sfac150
|View full text |Cite
|
Sign up to set email alerts
|

Kidney biopsy in lupus nephritis after achieving clinical renal remission: paving the way for renal outcome assessment

Abstract: The role of repeat kidney biopsy in lupus nephritis with renal remission is unclear. The aim of this study is to assess this role in a real-life scenario. This retrospective, single-centre study included 56 patients with lupus nephritis diagnosed from 1998 to 2019, with an initial kidney biopsy (KB1) at the onset of lupus nephritis and a second kidney biopsy (KB2) after achieving renal remission. Fifty-one (91.1%) patients were women with a median age of 29.9 [23.4–40.6] years at the time of lupus nephritis di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One study recently showed that despite reaching a perceived clinical remission by laboratory tests, 19.6% of patients had persistent activity on repeat renal biopsy. 19 This demonstrates the importance of finding alternative biomarkers of LN activity that can readily be used by physicians in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…One study recently showed that despite reaching a perceived clinical remission by laboratory tests, 19.6% of patients had persistent activity on repeat renal biopsy. 19 This demonstrates the importance of finding alternative biomarkers of LN activity that can readily be used by physicians in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of repeat kidney biopsies performed after the initial therapy have demonstrated a discordance between clinical and histological responses ( Fig 2 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 In the studies by Malvar et al 54 and Zickert et al, 55 where the histological response was defined as an activity index of 0 points by 6 to 8 months after the commencement of the initial immunosuppressive therapy, 18% (5/28) and 71% (12/17) of patients with complete response still had histological evidence of active kidney inflammation, respectively. Histological evidence of ongoing active kidney inflammation was observed in 20% (8/41) and 39% (7/18), respectively, of patients with partial response.…”
Section: The Post-therapy Kidney Biopsy: Histological Response Therap...mentioning
confidence: 99%
“…Monitoring of LN is done primarily on clinical grounds; however, there is often discordance between urinalysis, serological markers, and the underlying kidney histology [ 66 ]. In a cohort of 51 patients with complete renal response who underwent a second biopsy, residual low-grade histological activity (NIH activity index [AI] ≥ 2) was revealed in 11 (19.6%) [ 67 ]. In these patients, subsequent renal exacerbations were more frequent and occurred at an earlier time point as compared to their counterparts with AI < 2.…”
Section: Modifiable Risk Factors and Preventive Strategies For Lupus ...mentioning
confidence: 99%